From publics to practitioners: invention power and open technoscience - Papadopoulos, Dimitris (Taylor & Francis (Routledge), 2015)
There are more publics involved in science than one would imagine at first sight. In technoscientific conditions what counts as knowledge creation is not primarily the individual experimental achievement that gives coherence to scientific practice and separates science from its publics; rather, it is a form of dispersed experimentation in more than human worlds: distributed invention power. This form of labour involves intensive relationalities and transversal experimentation across different groups of people, other species and material environments. Distributed invention power is organised and regulated through the pervasive securitisation of technoscience: surveillance and control of technoscientific fields as well as financialisation of its activities and research outputs. The securitisation of science reorders the traditional split between the public sphere, the private sector and the commons. The folding of each one of these spheres into the other underlies a constant, often antagonistic, oscillation between big science and open science. What is constitutive of the diverse movements that sustain open technoscience is not that they challenge technoscience as such but that they try to create alternative knowledge practices inside different fields of technoscience. This distinction is of importance: it implies that a politics of publics can no longer be socially and materially transformative. What instigates transformation is the socially distributed and more than human experimentation with technoscience to create alternative forms of life.